Lowering risk for rice farmers to raise the water table in India - Deb, Proloy; Dubey, Swatantra; McCartney, Matthew P. (CGIAR, 2024)
This webinar presents the findings of research by the CGIAR Initiative on NEXUS Gains on farmers’ water application and water productivity under both direct-seeded rice and puddled transplanted rice across four districts in Haryana, India, as well as a case study on the co-benefits of crop diversification in the region. The results show how water savings can be achieved and can contribute to groundwater rejuvenation.